2021
DOI: 10.3389/fped.2020.624248
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Use of Anakinra in Multisystem Inflammatory Syndrome During COVID-19 Pandemic

Abstract: During COVID-19 outbreak, a large number of children with severe inflammatory disease has been reported. This condition, named Pediatric Multi-inflammatory Syndrome temporally associated with COVID-19 (PIMS-TS) or Multisystem Inflammatory Syndrome associated with Coronavirus Disease 2019 (MIS-C), shares some clinical features with Kawasaki disease and is frequently complicated by myocarditis or shock. It has been suggested that MIS-C belongs to the group of cytokine storm syndromes triggered by SARS-CoV-2 infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…More recently, case reports and case series of patients with MIS-C reported the efficacy of treatment with anakinra, highlighting its role particularly in those children who have insufficient response to IVIG and systemic glucocorticoids ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, case reports and case series of patients with MIS-C reported the efficacy of treatment with anakinra, highlighting its role particularly in those children who have insufficient response to IVIG and systemic glucocorticoids ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anakinra has been largely used and studied in the treatment of COVID-19 and is part of several clinical trials for this disease [ 13 , 14 , 15 ]; furthermore, its use has been described in a series of MIS-C cases, with good results [ 16 ]. Interestingly, successful use of anakinra in two cases of MIS-C refractive to IVIG and systemic glucocorticoids has also recently been described [ 17 ]. It could therefore prove useful for the treatment of MIS-A, a clinical entity for which established clinical practices are still foggy.…”
Section: Discussionmentioning
confidence: 99%
“…Anakinra is an IL-1 receptor antagonist that has been previously been shown to be effective with limited side effects in KD patients [57]. Multiple studies have shown anakinra to be similarly effective in MIS-C, especially when it comes to cardiac function, after failure or poor response to IVIG and steroid treatment [58][59][60]. In two large cohorts, anakinra was used in 24/186 and 8/183 patients to good effect [11, 13•].…”
Section: Immunomodulatory Therapiesmentioning
confidence: 99%